2018
DOI: 10.1159/000488571
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Targeting of the <b><i>SNCG</i></b> Gene Inhibits the Growth of Gastric Carcinoma SGC7901 Cells in vitro and in vivo<b> </b>by Downregulating the Phosphorylation of AKT/ERK

Abstract: The aim of the study was to evaluate the effects of synuclein-γ (SNCG) silencing on gastric cancer SGC7901 cells and to elucidate the associated mechanisms. pGCSIL-lentiviral siRNA targeting of the SNCG gene was employed to inhibit SNCG expression. Several experiments such as quantitative real-time PCR, Western blotting, MTT, colony formation, migration assay, and flow cytometry were performed to investigate the biological behavior of infected SGC7901 cells. BALB/c nude mice were used as tumor xenograft models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…First, we detected the mRNA and protein expression of SNCG in OSCC and found that SNCG was highly expressed in OSCC tissues, which was consistent with our previous study [ 24 , 25 ]. And our results were consistent with those reported in multiple articles, which indicate that SNCG was highly expressed in a variety of tumors [ 9 , 37 , 38 ]. However, our experimental results were inconsistent with those in the GEO database, and the results from the GEO database indicated that there was no difference in the SNCG expression between OSCC and normal tissues.…”
Section: Discussionsupporting
confidence: 93%
“…First, we detected the mRNA and protein expression of SNCG in OSCC and found that SNCG was highly expressed in OSCC tissues, which was consistent with our previous study [ 24 , 25 ]. And our results were consistent with those reported in multiple articles, which indicate that SNCG was highly expressed in a variety of tumors [ 9 , 37 , 38 ]. However, our experimental results were inconsistent with those in the GEO database, and the results from the GEO database indicated that there was no difference in the SNCG expression between OSCC and normal tissues.…”
Section: Discussionsupporting
confidence: 93%
“…To date, the overexpression of SNCG has been demonstrated in multiple malignant solid tumors, including breast, ovarian, uterus, liver, and cervical cancers [8][9][10]. Besides, SNCG up-regulation is related to tumorigenesis and metastasis [10][11][12]. Studies suggest SNCG may be a potential prognostic marker and therapeutic approach to promote cancer progression, but the association of the SNCG overexpression with patient survival is controversial in EOC [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we collected the breast muscle of male Jinghai yellow chickens at 4, 8 and 12 weeks for RNA-seq and found some growth related genes of male chicken. Common differentially expressed genes SNCG and ARHGDIB were mostly found to be related to cancer, and they can regulate cell proliferation, differentiation, invasion, metastasis and other cell behaviors [ 22 25 ]. So we speculated that the two genes may regulate the growth and development of chicken by influencing cell behaviors.…”
Section: Discussionmentioning
confidence: 99%